Influence of cyclist saddle setback on knee joint forces - Ménard, M.; Domalain,M.; Lacouture, P. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Despite the rapid development of bike fitting services, there is still a lack of scientific evidence on the effects of specific bicycle`s parameters on overuse injuries. The aim of this study was to investigate the influence of saddle setback on knee joint forces. Eleven cyclists experimented three saddle setback conditions while pedaling at a steady power output of 200 W and a cadence of 90 rpm. Using a static optimization procedure based on a musculoskeletal model, we estimated knee joint forces. As a first verification step, our preliminary results showed great similarity between muscle activations estimated from the modeling and experimental data (EMG) especially for the knee extensor muscles. Secondly, tibiofemoral joint forces tend to show that a forward sitting position increases tibiofemoral joint shear forces.